Grab Marketing Strategy, Research & Development - Gabriel Willy Widyatama; Shankar Chelliah; Yang Kai; Yang Yingxing; Yee Chew Tien; Wee Choo Mey; Liem Gai Sin (AIBPM Publisher, 2020)
Grab is a Singapore-based company providing transportation applications available in six countries in Southeast Asia. It utilizes smartphone cloud-based technology to provide ride-hailing and logistics services, food delivery, and courier service. This study proposes to determine and analyze the problems that exist in the Grab company. One of the problems in a company is a competition between companies. One of the competitors is GO-JEK. This research is expected to provide solutions to problems that exist within the company. How to stand out from competitors, attract more customers and drivers, and various training courses for drivers? What should the company decide on the price? In different countries, how should companies operate under different government policies?